Risks and mitigation options for on-site storage of wastewater from shale gas and tight oil development. (February 2017) - Kuwayama, Yusuke; Roeshot, Skyler; Krupnick, Alan; Richardson, Nathan; Mares, Jan
Abstract: We provide a critical review of existing research and information regarding the sources of risk associated with on-site shale gas and tight oil wastewater storage in the United States, the gaps that exist in knowledge regarding these risks, policy and technology options for addressing the risks, and the relative merits of those options. Specifically, we (a) identify the potential risks to human and ecological health associated with on-site storage of shale gas and tight oil wastewater via a literature survey and analysis of data on wastewater spills and regulatory violations, (b) provide a detailed description of government regulations or industry actions that may mitigate these risks to human and ecological health, and (c) provide a critical review of this information to help generate progress toward concrete action to make shale gas and tight oil development more sustainable and more acceptable to a skeptical public, while keeping costs down. Highlights: We review current research/information on shale gas and tight oil wastewater storage. Pit overflows, tank overfills, and liner malfunctions are common spill causes. Tanks lead to smaller and less frequent spills than pits, but are not a magic bullet. State regulations for on-site oil and gas wastewater storage are very heterogeneous.